Comparing Sodium Fusidate and Petrolatum for Electrosurgery-related Wound Healing: A Double-blind Randomized Controlled Trial - Parrol, Firman; Wibawa, Larisa Paramitha; Sitohang, Irma Bernadette Simbolon; Saldi, Siti Rizny Fitriana (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Electrosurgery is a common surgical technique used to treat skin tumors. This procedure produces necrotic skin, which might impair the wound healing process, prompting physicians to prescribe topical antibiotics to prevent infection. This study aims to analyze the efficacy of sodium fusidate ointment compared to petrolatum for wound healing after electrosurgery. Methods: We conducted a double-blind, randomized, controlled study with a within-person design. The inclusion criteria were adult subjects with seborrheic keratosis or acrochordon with a size of 4 mm to 10 mm on the face and neck, with a minimum of 2 lesions. Electrodessication was performed on the subject lesions. The patients were then randomized to receive and sodium fusidate ointment or petrolatum. Follow-up was done for up to 14 days, during which wound healing score, erythema, edema, crusts, re-epithelialization, incidence of infection, and subjective symptoms were assessed. This study is registered in ClinicalTrials.gov (NCT05353374). Results: Twenty-two subjects with 90 wounds were enrolled. The subjects had a mean age of 48.18 ± 11.25 years old and 86.4% of them had seborrheic keratosis. Statistical analysis revealed no significant difference in erythema, edema, crusts, re-epithelialization, infection, subjective symptoms, and total wound healing score appearance on days 3, 7, and 14 following the procedure. Conclusion: Both sodium fusidate ointment and petrolatum showed similar efficacy for wound healing after electrosurgery.